Comportamento ingestivo e consumo de forragem por novilhas de corte recebendo suplementos em pastagem de azevém - Rosa, Aline Tatiane Nunes da (2011)
Feeding behavior, forage intake by beef heifers, the pasture structure in two phenological stages of annual ryegrass (Lolium multiflorum): pre-flowering and flowering with heifers subjected to different feed systems: heifers exclusively on pasture or receiving corn grain (0.78% of body weight) or extruded fat (0.2% of body weight) as a supplement was studied. The experimental design was completely randomized in a factorial arrangement 3 x 2 (three supplements x two phenological stages of Italian ryegrass). The behavioral assessments were made by visual observation in four continuous 14 hour periods. Total DM and pastures intake were similar in both phenological stages. DM intake from pasture was higher for heifers consuming only ryegrass, intermediate for heifers that received fat, and lower when the supplement used was corn grain. Average daily gain of heifers was similar, regardless of the supplement received and the phenological stage of the ryegrass. The body condition score of heifers was similar in evaluations at pre-flowering and flowering stage of ryegrass. The heifers receiving corn grain had higher body condition score. The supply of corn grain caused a stocking rate 18% above other supplements tested. Grazing and ruminating time did not differ with the advance of the ryegrass cycle. Idle time was reduced from 312.22 to 228.68 minutes / day in the pre-flowering and flowering stage. The diurnal grazing, rumination and idle time were similar among heifers receiving different treatments.